2000
DOI: 10.1029/1999ja000383
|View full text |Cite
|
Sign up to set email alerts
|

Solar wind observations over Ulysses' first full polar orbit

Abstract: Abstract. This study examines solar wind plasma and magnetic field observations from Ulysses' first full polar orbit in order to characterize the high-latitude solar wind under conditions of decreasing and low solar activity. By comparing observations taken over nearly all hellolatitudes and two different intervals covering the same radial distances, we are able to separate the radial and latitudinal variations in the solar wind. We find that once the radial gradients are removed, none of the high-latitude sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
350
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 451 publications
(399 citation statements)
references
References 32 publications
48
350
1
Order By: Relevance
“…Therefore the annual variation in SW speed observed at 1 AU is not due to different speeds in the two magnetic hemispheres. This conclusion is in a good agreement with the rough equality of the average SW speed originating from the northern and southern coronal holes [McComas et al, 2000].…”
Section: Sw Speed In Magnetic Hemispheressupporting
confidence: 78%
“…Therefore the annual variation in SW speed observed at 1 AU is not due to different speeds in the two magnetic hemispheres. This conclusion is in a good agreement with the rough equality of the average SW speed originating from the northern and southern coronal holes [McComas et al, 2000].…”
Section: Sw Speed In Magnetic Hemispheressupporting
confidence: 78%
“…The first two polar passes between 1993 and 1997 occurred during the declining phase and minimum in activity cycle of the Sun. Highlights of the scientific returns of the first completion of the pole-to-pole pass have been recently summarized by McComas et al (2000). The most noted result pertaining to the study reported here was the predominance of the fast solar wind exceeding 650 km s Ϫ1 at latitudes above ‫03(ע‬Њ-40Њ).…”
Section: Introductionsupporting
confidence: 50%
“…If this occurs, then the conditions for instability are met, possibly causing the particle to slow rapidly to the observed situation of vc, p < VA. We will return to this point later in section 4, where we discuss a possible instability mechanism that may operate in this regime. We note that a similar argument is used by Goldstein et al [2000] in the context of proton-proton differential streaming to explain why the bulk of the observed proton-proton speed differences are considerably below the threshold for their proposed instability-driven damping mechanism.…”
Section: Reisenfeld Et Al' Helium Energetics' Ulysses Observationsmentioning
confidence: 94%